IMPLEMENTASI UNDANG UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI KOTA PEKANBARU (STUDI KASUS : KELANCARAN DAN KESELAMATAN LALU LINTAS) - Waldianto, Rahmi Illahi; Rusli, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Abstract: The Implementation of Law No. 22 of 2009 on Traffic and Transportation in the City of Pekanbaru (Case Study: Smooth and Traffic Safety). The purpose of this study was to determine the implementation of Law No. 22 of 2009 on Road Traffic and Road Transport in Pekanbaru City and the factors that influence it.The concept of the theory that the researchers use a policy and policy implementation. This study uses qualitative research methods to study descriptive data. In collecting the data, researchers use interviewing techniques, observation, literature study, and documentation. By using the snowball sampling technique as informants selection techniques and triangulation techniques as a source of testing the validity of the data.The results of this study indicate that the implementation of Law No. 22 of 2009 on Road Traffic and Road Transport in the field of safety and smooth traffic has been organized as well as possible by the Department of Communication and Information and Pekanbaru Police Traffic Unit, but the existence of complicated procedures and length and lack of traction officers provide sanctions for violators of traffic, and the presence of officers who violated procedures or offenders who mberusaha avoid sanctions, making the results less than the maximum expected. In addition, the lack of community participation to maintain the facilities, traffic infrastructure or assist in monitoring the traffic and the high order ego motorists in traffic also resulted in maximal implementation LLAJ Act.Keywords: Policy, Implementation, Traffic and Transportation (LLAJ)